A simple and sensitive LC‐MS/MS method for the determination of sotalol in rat plasma. (13th January 2015) - Feng, Zhiping; Yu, Siyuan; Liu, Wei; Yang, Li; Liu, Yang; Zhai, Suodi; Wang, Fang; Zhang, Xianhua
Abstract A sensitive, rapid and robust HPLC method with tandem mass spectrometry (HPLC/MS/MS) detection has been developed and validated for the quantification of sotalol in rat plasma. Plasma samples were precipitated with acetonitrile before analysis. The chromatographic separation was performed on an Atlantis hydrophilic interaction liquid chromatography Silica column (50 × 2.1 mm, 3 µm) with a gradient mobile phase of 10 mm NH4COOH (containing 0.2% of formic acid) as buffer A and acetonitrile as mobile phase B. Sotalol (m/z 273.2 → 255.1) and atenolol (the internal standard, IS, m/z 267.2 → 190.1) were monitored under positive ionization mode with 5500 QTRAP. Retention time of sotalol and the IS were 2.69 and 3.43 min, respectively. The linear range was 5–500 nm based on the analysis of 0.1 mL of plasma. The intrabatch precision ranged from 1.2 to 6.1%, and the inter‐batch precision was from 3.3 to 6.5%. The coefficient of variation of IS‐normalized matrix factor was 7.6%. Experiments for stability were performed and the analyte was sufficiently stable. A run time of 6 min for each injection made it possible to analyze a high throughput of plasma samples. The assay was successfully applied to the determination of sotalol in rat plasma after a micro‐dose oral administration. Copyright © 2014 John Wiley & Sons, Ltd.